A Literature Review on the Effect of Perceived Organizational Support on Employee Engagement and Employee Performance of Government Agencies in Singapore, Thailand and Indonesia - Rahmadani, Rahmadani; Rahim, Abdul Rahman; Prasilowati, Sri Lestari; Siradjuddin, Siradjuddin (International Journal of Social Service and Research, 2024)
The support of the organization where individuals work influences employees' quality of life in government agencies. Employee-perceived organizational support (POS) has been proven in previous research to help reduce employee stress levels and emotional exhaustion during work. The influence of POS in government agencies in Singapore, Thailand, and Indonesia shows similarities and differences. This research explores POS elements, namely Socio-emotional, Orientation towards organization and work, Behavioral outcomes, and Employee welfare, and its impact on government agencies in Singapore, Thailand, and Indonesia. The author uses a qualitative literature study approach; this research reveals POS elements practiced in government agencies in Singapore, Thailand, and Indonesia. The three countries theoretically use POS elements. However, in practice, their impact is very different, so the results of engagement and performance produced by employees are also different. The difference is that the POS implemented in Singapore and Thailand agencies contains a "behavior results" element, whereas in Indonesia, there is none. In Indonesia, nothing was found explicitly regarding the issue of cross-cultural citizenship behavior and employee withdrawal behavior. Furthermore, the POS measurement tool in the three countries uses the Survey of Perceived Organizational Support. The influence of POS fosters a positive work environment and can encourage employee satisfaction and work commitment. Therefore, agencies in Indonesia need to adapt it to increase employee engagement and performance